Enhancing Students’ Understanding of Science and Social Studies through Cooperative Learning Models at MI Syahid Al-Hidayah Salupangi: A Classroom Action Research - Harma; Hanipah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) explores the effectiveness of cooperative learning models in enhancing students’ understanding of Science and Social Studies (IPAS) at MI Syahid Al-Hidayah Salupangi. The study focuses on how cooperative learning, where students work together in small groups to achieve common academic goals, can improve engagement, comprehension, and academic performance in IPAS subjects. The research was conducted with a group of 5th-grade students, who were exposed to various cooperative learning strategies, including think-pair-share, jigsaw, and group discussions, during the IPAS lessons. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection. In each cycle, the teacher implemented different cooperative learning techniques to encourage active participation and collaborative problem-solving among students. Data were collected through observations, student performance assessments, and feedback from both teachers and students to evaluate the impact of the cooperative learning approach. The findings indicate that the use of cooperative learning models significantly improved students’ participation, motivation, and understanding of the IPAS material. Students were more engaged in the learning process, as the group activities allowed them to share ideas, ask questions, and learn from one another. Additionally, the cooperative learning environment fostered a sense of teamwork and responsibility, which led to better academic outcomes. The research highlights the importance of using active, student-centered learning approaches like cooperative learning to enhance the educational experience and outcomes for elementary school students.